ENVIRONMENTAL AND PERSONAL FACTORS AS PREDICTORS OF MARITAL ADJUSTMENT- AN INVESTIGATION IN PAKISTANI CONTEXT - Sana Lashari (Proceedings of The ICECRS, 2016)
Every individual wants to be gratified in his/her relations including marriage. Marriage is an important part of one's life as it effects social as well as emotional functioning of an individual. The present study aims to measure to investigate the roles of In-laws (experience with in- laws, husband’s supportive attitude and marital adjustment) in married life using correlation design. The questionnaires were given to 100 married women using snowball technique. Data was analyzed using SPSS version 16. The obtained results indicated a statistically significant positive relationship between the studied variables. Moreover, the study revealed a notable information about the role of relationship between the experience with in-laws and husband’s supportive attitude as a significant factor for successful marital adjustment and in developing a healthy relationship with in-laws. The study has implication for marriage counselors.